Pendekatan Saintifik Dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam Terhadap Siswa Kelas VII SMP Muhammadiyah 7 Medan - Sukria Hairun Nisa; Diva Sri Wahyuni Ahmad; Jahro Muniro (Yayasan Rahmat Islamiyah, 2023)
The application of a scientific approach in improving the learning outcomes of Islamic Religious Education for class VII students of SMP Muhammadiyah 7 Medan. The main problem in this study is the application of a scientific approach in learning Islamic Religious Education in class VII SMP Muhammadiyah 7 Medan, an overview of how the learning outcomes of class VII students of SMP Muhammadiyah 7 Medan. This study aims to find out how the application of a scientific approach in improving learning outcomes of Islamic Religious Education for class VII students of SMP Muhammadiyah 7 Medan. This research is a research that uses a qualitative approach to the type of descriptive research. Data collection techniques were carried out by observation, interviews and documentation. The results of this study indicate that the scientific approach in learning Islamic Religious Education in class in improving the learning outcomes of Islamic Religious Education for class VII students of SMP Muhammadiyah 7 Medan has long been well implemented because students use 5 stages namely: observing, asking, exploring, reasoning or associate and communicate.